Substitusi Jus Jeruk Segar Dengan Super Juice Jeruk Dalam Penerapan Mixology Berkelanjutan - Yusakh Yama Langi; Natal Olotua Sipayung; Syafruddin Rais; Rezki Alhamdi (CV. ITTC INDONESIA, 2025)
This study investigates the use of Super Juice as a substitute for fresh orange juice in sustainable mixology. The research employed a quantitative experimental method with a Completely Randomized Design (CRD) consisting of two treatments: fresh orange juice and Super Juice. Sensory evaluation was conducted by 30 panelists trained, semi-trained, and untrained who assessed color, aroma, taste, and texture using a five-point hedonic scale. Data were analyzed with the Mann Whitney U test in SPSS 19. The findings indicate no significant differences (p > 0.05) between the two samples across all sensory attributes. However, fresh orange juice showed slightly higher scores in color and taste, while Super Juice performed better in aroma and texture due to its acid-assisted extraction method. Overall, Super Juice obtained a marginally higher mean score, suggesting it can serve as an effective alternative that supports sustainable mixology by enhancing efficiency and reducing citrus waste..